Efektivitas Learning Cycle 3E Berkonteks Socioscientific Issues terhadap Pemahaman Konsep dan Penjelasan Ilmiah Siswa Sekolah Dasar - Dita Setya Arini; Sri Rahayu; Sentot Kusairi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This study aims to determine the effectiveness of the 3E learning cycle model in the context of socioscientific issues on conceptual understanding and scientific explanations of grade V students on science content. This study used a quasy experimental approach with posttest only control group design. The subjects of this study were fifth grade students in two public schools in Kalipare sub-district, namely SDN A and SDN B. The research instruments consisted a conceptual test of 20 multiple choice questions (α Cronbach’s = 0,842)  and 5 scientific explanation test with essay questions (α Cronbach’s = 0,882). The answers of scientific explanations are categorized using SOLO Taxonomy and tested by Cohen Kappa. Data analysis using ANOVA, Post Hoc further test and effect size. Product moment correlation test is used to see the correlation between understanding concepts and scientific explanations. The results of the study show that the 3E learning cycle model has socioscientific issues contexts that are effective in improving students' understanding of concepts and scientific explanations. Correlation analysis between understanding concepts and scientific explanations has a positive correlation.Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas model learning cycle 3E berkonteks socioscientific issues terhadap pemahaman konsep dan penjelasan ilmiah siswa kelas V pada muatan IPA. Penelitian ini menggunakan pendekatan quasy eksperimental dengan posttest only control group design. Subjek penelitian adalah siswa kelas V di dua sekolah negeri kecamatan Kalipare, yaitu SDN A dan SDN B. Instrumen penelitian terdiri dari tes pemahaman konsep 20 soal pilihan ganda dan 5 soal essay tes penjelasan ilmiah. Jawaban penjelasan ilmiah dikategorikan menggunakan Taksonomi SOLO dan diuji Cohen Kappa. Analisis data menggunakan uji ANOVA, uji lanjut Post Hoc, dan effect size. Uji korelasi product moment digunakan untuk melihat hubungan antara pemahaman konsep dan penjelasan ilmiah. Hasil penelitian menunjukkan bahwa model learning cycle 3E berkonteks socioscientific issues efektif untuk meningkatkan pemahaman konsep dan penjelasan ilmiah siswa. Analisis korelasi antara pemahaman konsep dan penjelasan ilmiah memiliki hubungan positif.